(untitled) (Herald of Journalism, 2018)
This article is devoted to a translation Abay’s «The Book of Words» into Russian language. The modern theory of translation is actively developing problems associated with the re-creation of the aesthetic quality of the original language. However, it must be noted that transfer does not always take into account the results of theoretical research: a clear confirmation of this is the translation of The Book of Words Abay. This work has been repeatedly translated into the Russian language for several decades. In the twenties, thirties, many works of Abay were translated into Russian. Quite a large number of translated works have been published on the centenary of his birth, But all of them have been implemented through interlinear, which affected the quality. In connection with this, there was a need for further research problems translations of Abay.